A morte vivida: o paradoxo da finitude em Jean-Paul Sartre - Gonçalves, Thiago Sitoni (2023)
Since 1930, Jean-Paul Sartre (1905-1980) has been keeping a lively interest in Psychology due to his philosophical writings. Since his immersion in Husserl’s phenomenology, the author critically redraws this epistemological relationship which circumscribes the human phenomena away from the positivist perspective and classic psychological science, starting from a concrete experience in the world. Thus, this research is based on the following enigma: how to describe the death phenomenon as a paradoxical experience revealed by finitude and comprehend a clinic in face of finitude? The research problem divides itself into two moments in Sartrean work, whether, initially, in his phenomenological psychology, or, secondly, his existential psychoanalysis. In opposing position to the “digestive” philosophy of French spiritualism, idealism and the classic theory that explains human actions by physiology, the young Sartre’s movement is to evoke, in the beginning, the return to the things themselves through the pre-reflective cogito. For this first moment of Sartrean work, we seek to comprehend his dialogue with phenomenology to describe the ultimate essence of consciousness. The emotion, image, dream and hallucination become an incarnational meaning in the world by an inextricable bond between consciousness-world, capable of a phenomenic description without using a transcendental Self (Husserlian sense) or an unconscious (psychoanalytic sense). In a second order, the research describes the conduct in the territory of freedom, intersubjectivity, bad-faith, anguish and responsibility written in Being and Nothingness from a new psychoanalytic approach, of an existential inspiration and engaged literature, described in What Is Literature? This is a double course of human reality analysis in its most radical dimension: the finitude. In the third chapter, we describe how the death theme presents itself to the philosopher in a limited situation, contextualized by the interwar period. We will untangle comprehension by phenomenology-existential philosophy about death and finitude and how we can describe them as a lived experience accompanied by the dynamism of consciousness. From the experience guided by prose, in the short story The Wall, we will follow the narrative of Pablo Ibbieta and his cellmates on the eve of his execution. The finitude’s paradox will happen by a human reality that questions its being and, even in a hard situation, in which death crumbles any positive sense of existence, there will be the appeal to freedom in inventing another way of existing. In this inventive and inspiring sense, we search in Sartrean contribution an enunciation of a psychological praxis in face of the finitude including the union between Sartrean philosophy and literature.